ANALISIS SPASIAL SEBARAN POTENSIAL DIRI BATUAN KAWASANMATA AIR PANAS - Rahma Hi. Manrulu; Aryadi Nurfalaq (Applied Physics of Cokroaminoto Palopo, 2020)
A research has been carried out with the title Spatial Analysis of the Potential Distribution of Rocks in the Hot Springs Area which aims to determine the potential distribution of rocks in the Pincara hot spring area and to determine the subsurface rock structure of the Pincara hot spring area based on the potential properties of the rocks. This study uses a Self Potential (SP) tool, by measuring the potential value at each measurement point, the potential value of surface temperature and the pH of hot water as supporting data. Retrieval of data for each measurement point using a fixed base technique (fix base). Potential data collection for daily correction is done by measuring the potential value at the same point repeatedly in a certain time interval. SP data collection points are 50 with a grid spacing of 5 meters. The results of the research in map 1 show that the characteristics of Pincara 1 hot springs have a surface temperature of 650C, smell of sulfur, there are boasting of gas bubbles, a measured pH of 7, while in map 2 the measured surface temperature of hot springs is 690C, clear, steamy, smelly. sulfur, visible boasting of gas bubbles, measured pH 8. The highest self potential value is 69.2 mV, the lowest self potential data is 1.2 mV. The average selfpotential in the study area has a value of 17.245 mV. This indicates the presence of igneous rock that causes anomaly. Igneous rock is rock that is conductive.